Screening and characterization of DNA aptamers that modulate prime editing - Wang, Mingxia; Wu, Xia; Huang, Xinbo; Ye, Jing; Gui, Yaoting (Frontiers in Molecular Biosciences, 2025)
IntroductionPrecise genome editing is a critical focus in gene therapy, and the CRISPR-Cas9 system has become a powerful and versatile tool for this purpose. However, a significant limitation of the CRISPR-Cas9 system is its low homologous recombination rate, which can impede the restoration of normal gene function. To address some of these challenges, advanced gene-editing technologies, such as base editors and prime editors have been developed. Here, we explored whether Cas9-specific single-stranded DNA (ssDNA) aptamers could enhance the PE2 system’s functionality.MethodsSystematic evolution of ligands by exponential enrichment (SELEX) was utilized to isolate high-affinity Cas9-specific ssDNA aptamers. Molecular docking simulations were subsequently performed to characterize the binding interactions between these aptamers and the PE2 protein. PE2 editing efficiency was quantitatively assessed using flow cytometry and Sanger sequencing. In bladder cancer cell lines, p53 mutation repair was evaluated by quantitative PCR and Western blot analysis, while cellular responses were examined through proliferation (CCK-8) and apoptosis assays.ResultsMolecular docking analysis revealed the interaction sites between SELEX-screened Cas9-specific aptamers and the PE2 protein. The incorporation of these aptamers significantly enhanced PE2 editing efficiency. In bladder cancer cells, the aptamer-PE2 complex effectively restored p53 function, leading to suppressed cellular proliferation and enhanced apoptosis rates.DiscussionOur study demonstrates that Cas9-specific aptamers can effectively enhance prime editing efficiency. This provide new insights into the modulation of prime editing and hold potential for improving its clinical applications.